2011
DOI: 10.1002/lary.22083
|View full text |Cite
|
Sign up to set email alerts
|

Enlarged vestibular aqueduct: Review of controversial aspects

Abstract: The enlarged vestibular aqueduct remains a controversial entity with variable presentation, progression, and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
106
2
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(116 citation statements)
references
References 73 publications
1
106
2
7
Order By: Relevance
“…Gopen et al [11] also mentioned that three long-term studies [12-14] reached similar conclusions. However, Emmett [15] and Zalza et al [16] obtained contradictory results; they reported that most of their patients had stable hearing.…”
Section: Introductionmentioning
confidence: 75%
“…Gopen et al [11] also mentioned that three long-term studies [12-14] reached similar conclusions. However, Emmett [15] and Zalza et al [16] obtained contradictory results; they reported that most of their patients had stable hearing.…”
Section: Introductionmentioning
confidence: 75%
“…An examination of the literature studies revealed that the hearing loss associated with IP-II and LVA malformations is heterogeneous, and the conductive component is not associated with middle ear pathologies [2,12,13,17,18,[20][21][22][23][24][25][26] . Roesch et al [25] found that patients with IP-II and isolated LVA malformations were diagnosed not only with severe to profound hearing loss but also with moderate asymmetrical hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigated the relationship between the size of the vestibular aqueduct and hearing loss, and different results were indicated [22,27,28] . Among these studies, Seo et al [28] found a correlation between the ABG and the size of the vestibular aqueduct.…”
Section: Discussionmentioning
confidence: 99%
“…Many adult patients with EVA may have not been diagnosed in the past due to lack of knowledge about the condition and availability of accurate imaging techniques [3]. Here, we report an interesting case of subsequent inadequate otological and audiological diagnosis leading to a profound hearing loss.…”
Section: Introductionmentioning
confidence: 97%